2020
DOI: 10.1186/s40510-020-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

RFA measurements of survival midpalatal orthodontic mini-implants in comparison to initial healing period

Abstract: Background: In dental implantology, the development of stability over time is a well-investigated topic. In case of orthodontic mini-implants, quantitative data for long-term stability is not available yet. This study aims to clinically investigate the long-term stability of mini-implants inserted in the midsagittal suture of the anterior palate. Moreover, the influence of the length of implants was elucidated. The stability of 2 × 9 and 2 × 11 mm miniimplants after orthodontic treatment (9 mm, 2.84 years ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
2
1
3
Order By: Relevance
“…However, the results of this study are in contrast with study done by Singh AK et al, 5 Song et al 21 and Neinkemper et al 22 They concluded that primary stability of mini implants is not affected by changes in length of mini implant. These differences in results found may be due to variation in brands of implants used, 5 or changes in diameter along with length of implants studied.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results of this study are in contrast with study done by Singh AK et al, 5 Song et al 21 and Neinkemper et al 22 They concluded that primary stability of mini implants is not affected by changes in length of mini implant. These differences in results found may be due to variation in brands of implants used, 5 or changes in diameter along with length of implants studied.…”
Section: Discussioncontrasting
confidence: 99%
“…3). Da die Langzeitstabilität medianer und paramedianer Implantate als gleich einzustufen ist [14,15,23], wird im beschriebenen digitalen Workflow die paramediane Insertion bevorzugt.…”
Section: Virtuelle Implantatplatzierungunclassified
“…Hierzu hat sich insbesondere die T-Zone im anterioren Gaumen des Oberkiefers als Insertionsregion medianer oder paramedianer Mini-Implantate etabliert [7][8][9] . In diesem Bereich gesetzte Mini-Implantate haben eine sehr gute Überlebensrate und verfügen über eine klinisch ausreichende und gut dokumentierte Langzeitstabilität [10][11][12][13][14][15].…”
unclassified
“…Polymer science has been the most popular field of study due to its vast applicability in engineering modern materials for the enhancement of structural and functional qualities in clinical and biomedical applications. A variety of polymers have optimal qualities, and the chemical modification of these polymers can improve their cytocompatibility, bioactivity, and antibacterial capabilities [ 12 , 13 ]. Several studies have revealed that polymeric materials may be used in tissue engineering to reconstruct cartilage, bone, and heart valves, and as skin, hip, and dental implants [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%